N-acyl 'Quat' pyrrolidinone auxiliary as a chiral amide equivalent via direct aminolysis - Davies, S; Dixon, D (1998)
A novel route into chiral amides is achieved through the efficient, non-racemising, cleavage of N-acyl side chains from a 'Quat' pyrrolidinone chiral auxiliary using a range of N-nucleophiles.